Learning Strategies in Making Video Project Assignments in ESP Class - Nurizzi Riqfi Ferdian (Linguists : Journal Of Linguistics and Language Teaching, 2019)
The development of digital video as one of the Information and Communication Technology (ICT) has crossed the threshold in the fields of education. In other words, the use of video has triggered teachers to use it in teaching and learning English. The purpose of the study was to investigate students’ learning strategies in making video project assignments conducted by students in an English for Specific Purposes class. Totally, 32 Informatics Management students who were taking English course in the ESP class at State Polytechnic of Subang. The data were collected via the questionnaire and the focus group discussion in which 8 students volunteered to participate. The results from the questionnaire analysis revealed that the students showed positive attitudes where they frequently used Cognitive strategies (x̄ = 3,98), Social strategies (x̄ = 3,84), Metacognitive strategies (x̄ = 4,15). The focus group interview revealed the ways the students employed the three strategies above, they liked to practice strategies of concepting the content, strategies of interpersonal cooperation, and strategies of recalling the concept. The study suggested that using various learning strategies in making video project assignments would benefit and the outcomes could be attributed to the proficiency level in both languages and making videos to master English that would be essential for students’ future career.Keywords: Learning Strategies, Video Project Assignments, Technology